Between Self Congruity, Destination Relationship and Memorable Tourist Experience: An Empiric Study on the Loyalty of Tourist Destination - Ardyan, Elia; Wibisono, Utomo (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2019)
This study examines the driving factors that can enhance tourist destination loyalty. Respondents used were 184 domestic tourists who had traveled to Bali. Data were analyzed using Structural Equation Modeling. Amos version 21 is used to process data. These results indicate that destination personality can improve the relationship destination but memorable tourist experience can not enhance it. The personality of a tourist destination enhance self-congruity. The study also found that memorable tourist experiences and the relationship destinations has a positive impact on increasing destinations loyalty. Self-congruity has a negative effect on destination loyalty. One contribution of this research related to showing the memorable tourist experience is more likely to influence loyal decisions than destination relationships.